Efektivitas Latihan Range of Motion (ROM) terhadap Kekuatan Otot pada Pasien Post-ORIF - Romdhoni Yoga Nugroho; Fahni Haris; Dwi Natalia Budiarti; Ria Novita Tresnawati (Universitas Muhammadiyah Klaten, 2026)
Background: Patients following Open Reduction Internal Fixation (ORIF) often experience decreased muscle strength due to postoperative immobilization, which may hinder functional recovery of the extremities. Range of Motion (ROM) exercises are non-pharmacological interventions that may help improve muscle strength. Objective: This study aimed to determine the effectiveness of ROM exercises in improving muscle strength among post-ORIF patients. Methods: This quantitative study employed a quasi-experimental design with a pre-test and post-test design without a control group. The sample are post-ORIF patients (n=6) who were treated in the surgical inpatient ward of RSUD dr. Tjitrowardojo Purworejo. ROM exercises were initiated on the first postoperative day and administered twice daily for 3 consecutive days, with each session lasting 15 minutes. Muscle strength was assessed using Manual Muscle Testing (MMT) and analyzed using the Wilcoxon Signed Rank Test. Results: The mean muscle strength score increased 0.83 point after the intervention. Statistical analysis showed a significant improvement in muscle strength following ROM exercises (p = 0.025; p < 0.05). Conclusion: ROM exercises are effective in improving muscle strength among post-ORIF patients and may be recommended as a nursing intervention during the inpatient recovery period.